ANALISIS MANAJEMEN LOGISTIK DI APOTEK BERSAMA DESA TUNTUNGAN II - Ramadhani, Lutfiah; Mahira, Clarissa Bunga; Ginting, Hermalia Putri Br; Hasibuan, Nurfaizah; Afrianda, Silvina Mutia; Nasution, Keyla Harista; Shafa, Banafsyah; Hasibuan, Rapotan (Jurnal Bina Bangsa Ekonomika, 2025)
Logistics management analysis in pharmacies is an important process to ensure efficiency in the management of drugs and health products. This study aims to evaluate the logistics management system or logistics management cycle applied in the Bersama Tuntungan II II pharmacy, by analyzing the process of planning, budgeting, procurement, storage, distribution or distribution, control, recording and reporting, to monitoring and evaluation. The method used in this study is a qualitative approach, with data collection through in-depth interviews with pharmacy staff and direct observation of the ongoing logistics process. The method used in this study is to use a qualitative approach, with data collection through in-depth interviews with pharmacy staff as well as the owner of the pharmacy and direct observation of the logistics process that takes place. The results show that pharmacies have implemented most of the standard operating procedures, but there are still some weaknesses, such as the lack of an integrated record-keeping system and the reliance on manual record-keeping. In addition, drug demand planning is still intuitive and not fully data-based. Based on these findings, it is recommended to implement digital-based technology to improve efficiency and accuracy in logistics management in pharmacies and implement a pharmaceutical management information system (SIMF) to improve data efficiency and accuracy, as well as conduct training for pharmacy staff related to effective logistics management.